2022
DOI: 10.3390/jcs6070203
|View full text |Cite
|
Sign up to set email alerts
|

Strain Control of Magnetic Anisotropy in Yttrium Iron Garnet Films in a Composite Structure with Yttrium Aluminum Garnet Substrate

Abstract: This report is on the nature of strain in thin films of yttrium iron garnet (YIG) on yttrium aluminum garnet (YAG) substrates due to film-substrate lattice mismatch and the resulting induced magnetic anisotropy. Films with thickness 55 nm to 380 nm were deposited on (100), (110), and (111) YAG substrates using pulsed laser deposition (PLD) techniques and characterized by structural and magnetic characterization techniques. The in-plane strain determined to be compressive using X-ray diffraction (XRD). It varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
(77 reference statements)
0
0
0
Order By: Relevance
“…Owing to their high melting point, high resistivity at room temperature ________ (10 12 Ωcm), low electromagnetic loss, and high thermal stability, YIGs are often used in applications at high frequencies [1]. Recently, YIG has been the subject of sensing applications [2][3][4][5][6][7][8], especially those in the form of granules and thin films. Since the 1980 s, D'Amico et al, [9][10][11] have shown that the presence of covalently unbalanced doped ions such as Ca 2+ , V 5+ , Sn 4+ , Zn 2+ , etc.…”
Section: Introduction *mentioning
confidence: 99%
“…Owing to their high melting point, high resistivity at room temperature ________ (10 12 Ωcm), low electromagnetic loss, and high thermal stability, YIGs are often used in applications at high frequencies [1]. Recently, YIG has been the subject of sensing applications [2][3][4][5][6][7][8], especially those in the form of granules and thin films. Since the 1980 s, D'Amico et al, [9][10][11] have shown that the presence of covalently unbalanced doped ions such as Ca 2+ , V 5+ , Sn 4+ , Zn 2+ , etc.…”
Section: Introduction *mentioning
confidence: 99%